The Role Of Traffic Police In Law Enforcement Hit And Run Criminal Study At Deli Serdang Police Station - Rudi Hariyono; T. Riza Zarzani (International Journal of Society and Law, 2024)
This study examines the role of the traffic police in law enforcement related to hit-and-run crimes within the jurisdiction of the Deli Serdang Police Department. Traffic violations, including hit-and-run incidents, remain a pressing issue that impacts road safety and public trust in law enforcement. Despite clear legal frameworks such as Article 312 of Law Number 22 of 2009 on Traffic and Road Transportation, challenges persist in identifying and prosecuting offenders due to factors like insufficient evidence and public reluctance to testify. This research aims to explore the efforts and obstacles faced by the traffic police in enforcing the law and mitigating hit-and-run crimes. The findings will contribute to enhancing law enforcement strategies and improving traffic safety outcomes.